RISK ANALYSIS OF LEMON CITRUS (Citrus limon) FARMING IN CIHAURBEUTI, CIAMIS - Mutiarasari, Nurul Risti; Nuryaman, Hendar; Salam, Rudhiana (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2024)
Lemon is known as a horticultural commodity that has the highest export value in Indonesia in 2021, reaching US 1,529 thousand with a production level of 2,513.86 tons. This lemon business opportunity can be a good prospect and has many benefits in various industries. Cihaurbeuti District is one of the lemon producing districts in Ciamis Regency, but there are fluctuations in production and fluctuations in prices. This happens because there are various farming risks such as production, cost, and income risks faced by farmers. The objectives of this study are to (1) identify the sources of risk of lemon farming, (2) analyze the level of risk of lemon farming, and (3) develop strategies that can be done by farmers in dealing with the risk of lemon farming in Cihaurbeuti District. The analysis model uses descriptive analysis and risk analysis (coefficient of variation). The results showed that there are four sources of risk identified in lemon farming, namelyweather and climate, pests and diseases, production facilities, andprice fluctuations. Based on the results of the analysis, the greatest level of risk faced in lemon farming is at the risk of costs with coefficient variation 3.32 (CV>0.5), it caused by fluctuations in input prices. The strategy carried out by farmers in dealing with production risk is done mechanically and chemically, while the cost risk strategy is to use a contingency budget, but has not done a handling strategy in the face of income risk.